Player-labelling as a solution to overcome maturation selection biases in youth football - Lüdin, D.; Donath, L.; Cobley, S.; Mann, D.; Romann, M. (Journal of Sports Sciences, 2022)
The fact that potentially skilled, but biologically later-maturing athletes are less likely to be selected into talent development programmes (TDP) can represent a failure of Talent Identification (TID) in sports. To overcome maturation selection biases, maturation independent TID should be established to include less mature, but talented athletes in TDP more frequently. Using a randomised parallel-group design, this study aimed to evaluate the effect of labelling under-11 (U11) Swiss male youth football players (n = 24, age = 11.0 ± 0.3 years) via maturation-ordered shirt numbers during rank assessment by talent scouts (n = 83, scout experience = 4.8 ± 2.4 years). Following observation of video recorded selection tournaments, player-labelling "informed" scouts were significantly more likely to rank less mature players higher on their player potential, t(81) = 2.57, p = .012, d = -0.6, 95% CI [-1.00, -0.13], than "uninformed" scouts. As altered rankings assisted less mature players, player-labelling may offer a practical and feasible strategy to improve TID by removing possible maturation selection biases. To address maturation selection biases and the potential positive impact of player-labelling more broadly, further research on both male and female athletes in various age categories and sports contexts is recommended.